A novel method for the measurement of degenerative chain transfer coefficients: proof of concept and experimental validation. Issue 19 (25th April 2016) - Derboven, Pieter; Van Steenberge, Paul H. M.; Reyniers, Marie-Françoise; Barner-Kowollik, Christopher; D'hooge, Dagmar R.; Marin, Guy B.
Abstract : A novel method is presented to determine transfer coefficients in degenerative reversible addition fragmentation chain transfer (RAFT) polymerization from experimental dispersity data. Abstract : A novel method is presented to determine transfer coefficients in degenerative reversible addition fragmentation chain transfer (RAFT) polymerization from experimental dispersity data. Both the exchange reactivity with the small RAFT agent (CTA; C tr, 0 ) and the macro-RAFT agent ( C tr ) can be measured at specific monomer conversions. The method is able to capture for the first time a possible intrinsic or apparent chain length dependency of C tr(0) or thus the RAFT addition rate coefficient, an outstanding challenge in the mechanistic understanding of RAFT polymerization up to high monomer conversion. In its development stage, the method has been theoretically evaluated via the simulation of test cases in the absence and presence of artificial error. Experimental data at 353 K for azobis(isobutyronitrile) (AIBN) initiated RAFT polymerization of methyl methacrylate (MMA) with cyano-2-propyl dithiobenzoate (CPDB) as a small RAFT agent are successfully analyzed with the novel method. A highly accurate value of 20 is obtained for the exchange with CPDB. For the RAFT exchange with the macro-RAFT agent, an approximate but higher value of 76 is obtained and no chain length dependency is detected. The method is implemented in a spreadsheet, including a step by step explanation of the input parameters.